2015
DOI: 10.1186/s12879-015-0907-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bloodstream infection in patients at a Brazilian hemodialysis center: a case–control study

Abstract: BackgroundInfection is the leading cause of morbidity and the second leading cause of mortality in patients on renal replacement therapy. The rates of bloodstream infection in hemodialysis patients vary according to the type of venous access used. Gram-positive bacteria are most frequently isolated in blood cultures of hemodialysis patients. This study evaluated risk factors for the development of bloodstream infections in patients undergoing hemodialysis.MethodsRisk factors associated with bloodstream infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
52
3
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 31 publications
12
52
3
6
Order By: Relevance
“…With regard to the resistance profiles, we found that 33.3% of the Enterobacteriaceae isolated were multidrug-resistant (MDR) and that 20% of the Staphylococcus aureus isolated was methicillin-resistant (MRSA). The prevalence of MDR Enterobacteriaceae found in this study is similar to the 36.4% resistance rate reported by Fram et al [18]. On reviewing the literature, the resistance of S. aureus varied from 2.1 to 38.5% [14,18].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…With regard to the resistance profiles, we found that 33.3% of the Enterobacteriaceae isolated were multidrug-resistant (MDR) and that 20% of the Staphylococcus aureus isolated was methicillin-resistant (MRSA). The prevalence of MDR Enterobacteriaceae found in this study is similar to the 36.4% resistance rate reported by Fram et al [18]. On reviewing the literature, the resistance of S. aureus varied from 2.1 to 38.5% [14,18].…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of MDR Enterobacteriaceae found in this study is similar to the 36.4% resistance rate reported by Fram et al [18]. On reviewing the literature, the resistance of S. aureus varied from 2.1 to 38.5% [14,18]. Nevertheless, MRSA has been reported in hemodialysis outpatient facilities, and every effort must be made to reduce the spread of MDROs as they are associated with higher rates of morbidity and mortality [19].…”
Section: Discussionsupporting
confidence: 70%
“…It is unclear whether the ratio of resistant bacteria in hemodialysis patients is higher than that in the general population. In a single-center report from Brazil in 2010-2013, 38.5% of S. aureus was MRSA[25], whereas the methicillin resistance percentage was 31.0% in surveillance data from Brazil in 2005-2008[26]. However, a national surveillance report for England indicated that the relative risk of MRSA bacteremia was approximately 100-fold higher for dialysis patients than for the general population and was 8-fold higher for patients using a catheter than for those with an arteriovenous fistula[27].…”
Section: Causative Organismsmentioning
confidence: 99%
“…Santral kateter ilişkili kan dolaşımı enfeksiyonunun insidansı 1000 kateter gününde 2,9 ile 17 arasında değişmektedir [25,26] . Santral kateter ilişkili kan dolaşımı enfeksiyon insidansını, YBÜ'lerin kapasitesi, iş yükü, hastaların alt hastalıkları, mevcut hastalığın ağırlığı gibi faktörler belirlemektedir [27] . Ancak, yapılan çalışmalarda enfeksiyon kontrol demet uygulamaları ile SKİ-KDE hızının sıfıra indirilebileceği gösterilmiştir [28,29] .…”
Section: Santral Kateter İlişkili Kan Dolaşımı Enfeksiyonu öNleme Demetiunclassified